A DIMENSIONLESS VENT NUMBER CHARACTERIZING THE THERMAL IMPACT OF FLUID DISCHARGE THROUGH PLANAR AND CYLINDRICAL VENTS WITH PARTICULAR APPLICATION TO SEAFLOOR GAS VENTS CRYSTALLIZING HYDRATE - Cathles L.M.; Chen D.F.; Nicholson B.F. (My University, 2006)
A dimensionless vent number is derived that characterizes the axial temperature changes caused by vertical heat advection in vent zones of planar or cylindrical shape and horizontal dimensions of meters to hundreds of meters or more. The vent number, N v depends on the depth extent and width of the vent zone and the rate and duration of venting and is applicable to many common geologic situations such as mud and salt diapirism. and gas venting. It provides an easy way to estimate the thermal consequences of venting in cases where the geometry of the vent and its rate and duration of discharge can be estimated. Temperature perturbations are minimal for N v < 0.1. For N v > 2 the temperature profile along the vent zone axis follows the one-dimensional steady state advection profile and horizontal heat losses are negligible. Use of vent numbers is illustrated by assessing the thermal impact of gas venting at the Bush Hill hydrate mound offshore Louisiana. The analysis shows that the temperature perturbations expected from the gas venting there are very small and that any subsurface temperature increase in the area was likely caused by the mud diapirism. that preceded the gas venting. The subsurface should be cooling and hydrate crystallizing to progressively greater depths during the ensuing period of gas venting. These conclusions are not obvious but are easily reached using vent numbers. Copyright 2006 by the American Geophysical Union.